The History of the Reformation of the Church in the 16th Century and Its Influence on the Church Today - Yerlin Vinni Sutri; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2021)
The history of the reformation of the church is a very long and very memorable history for the church. The Reformation was an attempt by the reformers to return the church to biblical authority. The life of the church before the reformation was very far from the truth of the Bible, where church leaders carried out deviations and heretical teachings. Many church leaders take advantage of their position to gain profit, for example the sale of a pardon. Luther invited people at that time to turn to the true teachings of the Bible. Outside of Martin Luther, there were also reformers who continued Luther's work, namely John Calvin and Ulrich Zwingli. After 500 years of church reformation, the church today is still feeling the effects of the reformation although there are still churches that deviate from the teachings of the Bible. The church reformation changed wrong mindsets and views and brought believers to the true truth of the Bible. The results of the reformation brought believers to the true knowledge of Jesus Christ. The situation before the reformation and after the reformation is very different, where the entire leadership in the church has been changed. Leaders in the church today are not only governed by the pastor but also by people who have been chosen and determined.